Process of Transitivity in Agoda’s Caption Related to Lodging Terminology: A Systemic Functional Study - Nova Asyri Aryanti; Humaira Restu Maulidia; Mayang Pramudhita (Soegijapranata Catholic University, 2021)
This research aims to describe the process of transitivity found in Agoda’s caption related to lodging terminology and to find out what types of processes are mostly found in Agoda’s caption related to lodging terminology. It is descriptive research, where the data of the research was from Agoda’s official Instagram account. The result of the research found that the types of processes that appeared in the data were material, mental, behavioral, relational, and verbal processes. The material process is the one mostly found in the data.